Evaluation of the contemporary aesthetic education value of Chinese classical dance education thought - Wen Qi; Yunxia Ma (Trans/Form/Ação)
Chinese classical dance education has a profound impact on contemporary aesthetic education. Its educational philosophy of "neutralization" and "twin" can provide a unique value perspective and practical path for modern aesthetic education. This paper explores the aesthetic education concept of Chinese classical dance and its educational value in contemporary society, aiming to improve the individuals’ moral quality and humanistic one through dance education. Starting from analyzing the origin, development and vitality of Chinese classical dance, this paper explores its aesthetic education concept and its contemporary aesthetic value from the perspectives of dance education, harmony, cultivation, and integrated education. The study believes that bridging the gap between Chinese traditional dance education concepts and contemporary aesthetic education, and combining classical dance philosophy with modern dance practice, can greatly improve the aesthetic education level of modern dance. Integrating philosophical reflection into dance research can deepen the understanding of the cultural significance and aesthetic value of dance.